A novel germ-line mutation in p53 gene - Roesler, Wojciech; Przybyła, Anna; Mackiewicz, Andrzej; Lamperska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2006)
Germline mutations of p53 gene are rare, worldwide there are reported about 283 of such changes. They are strongly connected with Li-Fraumeni and Li-Fraumeni Like syndromes. They also may appear in multicancer syndrome. The aim of this study was to establish frequency of p53 mutations in multicancer families in polish population. DNA was extracted from patient’s peripheral blood samples. Mutations were analyzed employing the PCR-SSCP method with 7 pairs of radioactive primers, which covered exons 2-11. DNA fragments showing a different migration pattern were sequenced. In one case we found a change in exon 11 of p53 gene. A mutation was identified as adenosine insertion in codon 385 which caused an alteration of amino acids from 385 to 389. The STOP codon appeared in position 390 causing shorter p53 protein. This mutation was found in one of 38 cases and frequency of this mutation was establish on 2.6%. Insertion A in codon 385 did not appear in p53 mutational database IARC. Moreover, no mutations in exon 11 were reported in this database. Based on the family interview with the carrier we concluded that insertion A in exon 11 was not involved in cancer phenotype.